Peer influence on adolescents behavior - Elias, Habibah; Mahyuddin, Rahil (Common Ground Publishing, 2008)
Papalia, et.al (1998) argued that as children begin to move away from parental influence, the peer group will open up new perspectives. By involving themselves in peer activities, children can test values they hold. On the other hand, Papalia (1998) also discussed the negative effets of peer groups. To be a member of a peer group, an adolescent must accept the values and behavioral norms even though these may be undesirable. The pressure to conform can also lead to troublesome adolescent and even a delinquent one. This study will focus on the At-Risk adolescents. The respondents were 16 year-old students from Malaysian government secondary schools. Total respondents were 113 students, from 25 schools. Each school were represented between 4- 5 students selected by the school counselors based on several characteristics such as low performance in school, involvement in discipline problems and potential dropouts. These students were interviewed by the researchers. Results showed that through peer influence, the adolescents indulged in several misbehaviors such as, smoking, fighting, stealing, truancy, loitering around school compounds. All of these adolescents were under achievers and did not perform in their school examinations.